Peningkatan Pengetahuan Kader Posyandu dalam Manajemen Laktasi Melalui Metode Ceramah di Kelurahan Rangkapan Jaya Kecamatan Pancoran Mas Kota Depok - Astuti, Nurul Huriah (ARKESMAS (Arsip Kesehatan Masyarakat), 2017)
Knowledge Improvement of Posyandu Cadres in Lactation Management Through Lecture Method in Rangkapan Jaya Village, Pancoran Mas Sub-district, Depok City Introduction : Mother’s Milk is the first food for babies and provides energy and nutrients not only for the first six months of life but also up to two years of age. Breastfeeding is one of the most effective ways to ensure the health and survival of the child. Indonesia Demographic and Health Survey 2012 states that the exclusive breastfeeding rate was 42% in Indonesia, 33.7% in West Java, and 61.36% in Depok City. This numbers need to be improved. One way is through health cadres in Posyandu as the front guard to improve public health status. This study aims to determine the effectiveness of lecture methods with such tools in improving knowledge about lactation management. Methods : The subjects of this study were 24 health cadres at four posyandu in Rangkapan Jaya Village Pancoran Mas Sub-district Depok City. This type of research is quasi experimental with pre-test and post-test design. Results : The results showed that 87.5% of respondents had improved knowledge after training with lecture and demonstration methods with props and emo-demo techniques. The average pre-test score was 85.88 and post-test score was 91.08. Respondents who had a range of knowledge score 90-100 were higher on post-test result (62.5%) than pre-test result (29.2%). The results of statistical tests showed that there was difference of cadres knowledge between before and after being given lactation management training through lecture and demonstration methods with props and emo-demo techniques (p = 0.004). Conclusions : The results showed that 87.5% of respondents had improved knowledge after training with lecture and demonstration methods with props and emo-demo techniques. The results of statistical tests indicate that the methods performed effectively increase the knowledge of health cadres. Continuing education for posyandu health cadres through lecture and demontration methods with props and emodemo techniques can bean option.